Nutriquest 2.1 : your electronic guide to good nutrition and health - Kane, Kevin, 1954- (Iowa : McGraw-Hill Higher Educations, 2000)
This program allows you to track daily food intake, energy expenditure and to create weight-management goals. Several different report and pie charts allows you to see the nutritional breakout for specific food, meals, one day or an average of several days.
This CD-ROM is also available at Makmal Multimedia, Perpustakaan Perubatan.
System requirements : Windows : IBM-compatible computer, 486, 50 Mhz processor or better, 16 MB RAM, 20 MB of available hard disk space, Windows 95 or higher, 640 x 480 x 256 color display or higehr, CD-ROM drive.
Keywords: Nutrition; Health; Food